2006
DOI: 10.1080/00365520600548966
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal nitric oxide synthase activity changes during experimental colon obstruction

Abstract: The motility of the colon was either significantly increased or decreased, depending on the type and selectivity of the NOS inhibitor compounds applied. NO of neuronal origin is a transmitter that stimulates peristaltic activity; but an increased iNOS/nNOS ratio significantly moderates the obstruction-induced motility increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In this canine model, experimental blockade of the intestinal passage increased the large bowel motility, and triggered a hyperdynamic circulatory reaction 5 h after obstruction, accompanied by significant NO production, XO activation and leucocyte accumulation in the proximal colon. This hyperdynamic cardiovascular response may be regarded as a compensatory reaction through which the organism tries to accommodate to the evolving septic metabolic changes 28,29 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this canine model, experimental blockade of the intestinal passage increased the large bowel motility, and triggered a hyperdynamic circulatory reaction 5 h after obstruction, accompanied by significant NO production, XO activation and leucocyte accumulation in the proximal colon. This hyperdynamic cardiovascular response may be regarded as a compensatory reaction through which the organism tries to accommodate to the evolving septic metabolic changes 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…32 have demonstrated that low doses of endotoxin cause marked changes in myoelectric activity in the small intestine, with repetitive bursts of spike potentials and a simultaneous increase in the transit of the intestinal contents. Indeed, the obstruction‐induced motility alterations are time‐dependent, characteristically changing in parallel with the development of inflammation 28,33,34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations